E-Justice: European Standards and the State of Implementation in Ukraine - Згама, Антоніна Олександрівна; Згама, А. О.; Згама, Антонина Александровна; Zghama, Antonina O.; Стеценко, Семен Григорович; Стеценко, С. Г.; Стеценко, Семен Григорьевич; Stetsenko, Semen H.; Пилипенко, Світлана Анатоліївна; Пилипенко, С. А.; Пилипенко, Светлана Анатольевна; Pylypenko, Svitlana A.; et al. (Allied Business Academies, 2019)
The authors study the issues of European standards for the implementation, functioning and improvement of the e-justice system, as well as the current state of legislative support and effectiveness of e-court in Ukraine in the light of European integration processes. The main stages of the implementation and improvement of the e-justice system in the European Union are highlighted by considering the main provisions of the E-Justice Strategies 2008, 2009-2013, 2014-2018 and 2019-2023. Special attention is paid to the special features of the functioning of the existing European e-Justice Portal. The historical aspects of the implementation of the concept of “e-court” in Ukraine are outlined. The main focus is on the main goals of improving the judicial system in accordance with the Strategy for the Development of the Judiciary of Ukraine 2015-2019 in general and on e-Justice in particular. The issues of implementation of the Unified Court Information and Telecommunication System are considered with the purpose of promptness, predictability and convenience of interaction between the court and participants of the trial.

Автори досліджують питання європейських стандартів впровадження, функціонування та вдосконалення системи електронного правосуддя, а також сучасний стан законодавчого забезпечення та ефективності електронного суду в Україні у світлі євроінтеграційних процесів. Основні етапи впровадження та вдосконалення системи електронного правосуддя в Європейському Союзі висвітлено з огляду на основні положення Стратегій електронного правосуддя на 2008, 2009-2013, 2014-2018 та 2019-2023 роки. Особливу увагу приділено особливостям функціонування існуючого Європейського порталу електронного правосуддя. Окреслено історичні аспекти реалізації концепції «електронного суду» в Україні. Основна увага приділяється основним цілям удосконалення судової системи відповідно до Стратегії розвитку судоустрою України на 2015-2019 роки в цілому та електронного правосуддя зокрема. Питання впровадження Єдиної судової інформаційно-телекомунікаційної системи розглядаються з метою оперативності, передбачуваності та зручності взаємодії суду та учасників судового розгляду.
Stetsenko S. E-Justice: European Standards and the State of Implementation in Ukraine / S. Stetsenko, S. Pylypenko, A. Zghama, E. Sydorova, S. Shkliar // Journal of Legal, Ethical and Regulatory Issues. - Vol. 22. - Issue 5. -Allied Business Academies, 2019. - P. 1–6.
Keywords: E-justice; Е-court; European e-Justice Portal; Unified Judicial Information; Telecommunication System; електронне правосуддя; е-суд; Європейський портал електронного правосуддя; Єдина судова інформація; телекомунікаційна система; Research Subject Categories::LAW/JURISPRUDENCE